-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathassignment2intrn.tex
119 lines (65 loc) · 3.38 KB
/
assignment2intrn.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
\documentclass[a4paper,12pt]{article}
\usepackage{amsmath}
\begin{document}
\title{Assignment 2}
\author{Junaid Ahmad Bhat}
\date{\today}
\maketitle
\section*{\small Question}
If A and B are square matrices of the same order such that AB=BA, then prove by induction that \textit{AB $^n$=B $^n$A.} \\
Further, prove that \textit{(AB)$^n$=A $^n$B $^n$} for all n$\epsilon$N.\\
\section*{\small Solution}
A and B are square matrices of the same order such that AB=BA\\
To prove: P(n):\textit{AB$^n$=B$^n$A},n$\epsilon$N\\
For n=1, we have:\\
P(1):\textit{AB=BA} [Given]\\
\textit{AB$^1$=B$^1$A}\\
i,e the result is true for n=1.\\
Let the result be true for n=k.\\
P(k):\textit{AB$^k$=B$^k$A} \hspace{4cm}(1)\\
Now, we prove that the result is rue for n=k+1.\\
\textit{AB $^k$$^+$$^1$=AB$^k$.B=(B$^k$A)B} (By(1))\\
\hspace{4cm} =\textit{B$^k$(AB)} \hspace{2cm}(By Associative law)\\
\hspace{4cm} =\textit{B$^k$(BA}) \hspace{2cm}(AB=BA (given))\\
\hspace{4cm} =\textit{(B$^k$B)A} \hspace{2cm}( By Associative law)\\
\hspace{4cm} =\textit{B $^k$$^+$$^1$A}\\
i,e the result is true for n=k+1.\\
Thus, by the principle of mathematical induction ,
we have \textit{AB $^n$=B$^n$A},n$\epsilon$N.\\
Now, we prove that \textit{(AB$^n$)=A $^n$B $^n$} for all n$\epsilon$N\\
For n=1, we have:\\
\textit{(AB) $^1$=A $^1$B $^1$=AB}\\
i,e the result is true for n=1.\\
Let it be true for n=k.\\
\textit{(AB) $^k$=A$^k$B$^k$} \hspace{4cm}(2)\\
Now we prove that the result is true for n=k+1.\\
\textit{(AB)$^k$$^+$$^1$=(AB)$^k$.(AB)=(A $^k$B $^k$)(AB)}.\hspace{2cm} (By (2) )\\
\hspace{4cm} \textit{=A$^k$ (B$^k$ A)B} \hspace{2cm}( By Associative law)\\
\hspace{4cm} =\textit{A$^k$(AB$^k$)B} \hspace{2cm}(AB$^n$=B$^n$A, n$\epsilon$N)\\
\hspace{4cm}=\textit{(A$^k$A).(B$^k$B)} \hspace{2cm}(By Associative law)\\
\hspace{4cm}=\textit{A$^k$$^+$$^1$B$^k$$^+$$^1$}\\
i,e the result is true for n=k+1.\\
Therefore, by the principle of mathematical induction , we have \textit{(AB)$^n$=A$^n$B$^n$},\\
for all natural numbers.
\section*{{\small Question}} Let A=$\begin{pmatrix} 0 & 1 \\ 0 & 0 \end{pmatrix}$ ,show that \textit{(aI + bA)$^n$= a$^n$I+na$^n$$^-$$^1$bA},where I is tha identity matrix of order 2 and n$\epsilon$N.
\section*{{\small Solution}}Using principle of mathematical induction\\
For n=1,we have\\
\textit{P(1):(aI+bA)=aI+a$^0$bA=aI+bA}\\
i,e
result is true for n=1\\
Let it be true for n=k\\
i,e
\textit{P(k):(aI+bA)$^k$=a$^k$I+ka$^k$$^-$$^1$bA}\\
Now,we have to prove the result is true for n=k+1.\\
\textit{(aI+bA)$^k$$^+$$^1$=(aI+bA)$^k$(aI+bA)}\\
\hspace*{2.2cm} \textit{=(a$^k$I+ka$^k$$^-$$^1$bA)(aI+bA)}\\
\hspace*{2.2cm} \textit{=a$^k$$^+$$^1$I+ka$^k$bAI+a$^k$bIA+ka $^k$$^-$$^1$b$^2$A$^2$}\\
\hspace*{2.2cm} \textit{=a$^k$$^+$$^1$I+(k+1)a$^k$bA+ka$^k$$^-$$^1$b$^2$A$^2$} \hspace{3cm}(1)\\
Now,
A$^2$=$\begin{bmatrix} 0 & 1 \\ 0 & 0 \end{bmatrix}$ $\begin{bmatrix} 0 & 1 \\ 0 & 0 \end{bmatrix}$=$\begin{bmatrix} 0 & 0 \\ 0 & 0 \end{bmatrix}$=0\\
Therfore,eqn(1) becomes\\
\textit{(aI+bA)$^k$$^+$$^1$=a$^k$$^+$$^1$I+(k+1)a$^k$bA}\\
Hence proved result is true for n=k+1\\
Therefore, by principle of mathematical induction we have\\
\textit{(aI + bA)$^n$= a$^n$I+na$^n$$^-$$^1$bA}\\
\end{document}